Analysis of interface states of GaAs-rhodamine hybrid diode by Hill-Coleman method - Cavas, Mehmet (Pergamon-Elsevier Science Ltd, 2013)
The interface states properties of a hybrid diode based on GaAs and Rhodamine organic semiconductor were investigated by current-voltage and capacitance-conductance-voltage measurements. The Al/Rhodamine/p-GaAs diode exhibits a rectification behavior with the barrier height value of 0.794 eV and ideality factor of 1.45. The interface states density of the diode was determined by Hill-Coleman method. The D-it value is decreased with increasing frequency. It is seen that the electronic parameters of the Al/Rhodamine/p-GaAs diode are significantly different from the conventional Al/p-GaAs Schottky diode. This indicates that Rhodamine organic semiconductor controls the interface properties of Al/p-GaAs Schottky diode. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Electronic materials; Schottky diode; Electrical properties